Large scale preparative electrophoresis equipment: the current state-of-the-art - Mat, Hanapi; Stitt, E.H.; Abdul Mutalib, Mohamed Ibrahim (1989)
Progressive development in genetically-engineered biotechnological products in general and downstream processing in particular, has prompted the development of large scale electrophoresis equipment due to its capability and versatility to separate biochemical products. In this paper, large scale electrophoresis equipment and its important in downstream processing with respect to its development, current status and future prospect are reviewed.